The application of acoustic emission for detecting incipient cavitation and the best efficiency point of a 60 kW centrifugal pump: case study - Alfayez, L; Mba, David; Dyson, G (Elsevier Science B.V., Amsterdam., 2005)
Pumps play a significant role in industrial plants and need continuous monitoring to minimise loss of production. To date, there is limited published information on the application of acoustic emission (AE) to incipient pump cavitation. This paper presents a case study where AE has been applied for detecting incipient cavitation and determining the best efficiency point (BEP) of a 60 kW centrifugal pump. Results presented are based on net positive suction head (NPSH) and performance tests. In conclusion, the AE technique was shown to offer early detection of incipient cavitation, furthermore, the technique has demonstrated the ability to determine the BEP of a pump.
Keywords: Acoustic emission; Best efficiency point; Cavitation; Condition monitoring; Pump performance